Anders Breivik et le « marxisme culturel » : Etats-Unis/Europe - Jérôme Jamin (Amnis)
The terrorist attacks in Oslo planed by Anders Breivik in July 2011 have set off multiple debates and comments on the profile and the motivations of the person, on the specific identity of its selected victims – elites and future political elites –, but also on the mental health of the concerned individual. Without taking into account any psychological or psychoanalytical factors, and based on discourse and speech analysis, this article seeks to understand and describe the ideological environment in which Breivik has evolved. At the origin, and at the core of its e-book released a few hours before the attacks, we first discover an abounding literature that is born in the United States right after the collapse of communist regimes. This literature is at war with « multiculturalism », « cultural Marxism » and the « political correctness » seen as an ideology; it will cross the ocean during the nineties thanks to the Internet; and will finish its trip in a vast European blogosphere full of conspiracy theories on the « islamization » of the world. At the end, the article shows how the disappearing of the White Christian West (Europe and the United States) as planned by multicultural elites of both Bruxelles and Washington is at the core of Anders Breivik vision of the world.